Spontaneous hemoperitoneum and digestive hemorrhage determined by sigmoidal simple ulcer. - Croci, Fabio; dos Santos, Gustavo; Rabellino, Joaquín; Kamaid, Emil; Cordal, Adriana (Cirugía del Uruguay, 1985)
Description of a case of a sigmoidal colon ulcer complicated with digestive hemorrhage, blocked perforation and hemoperitoneum, the last one being an exceptional occurrence, the probable pathogeny of which is related to vascularities. The subject is thoroughly examined which is justified account taken of its very low incidence.